Tinjauan Yuridis Penggunaan Rekaman CCTV sebagai Bukti dalam Perkara Pidana - Nofrianto Adi Aryo Nope; Ida Bagus Anggapurana Pidada; Ni Made Rai Sukardi (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
This study, entitled "A Legal Review of the Position of CCTV Recordings as Evidence in the Investigation and Proving of Criminal Cases (A Case Study at the Rembang Police Department and the Rembang District Court), aims to determine the position of CCTV recordings as evidence in the investigation and proving of criminal cases at the Rembang Police Department and the Rembang District Court. It also aims to identify the obstacles and solutions faced by the police and judges in the investigation and proving of criminal cases through CCTV recordings. The research method uses a sociological legal approach. Data sources were obtained through several stages, namely field research (interviews) and library research. Data analysis was carried out systematically, including data reduction, data presentation, and drawing conclusions. Based on the research results, it can be concluded that the position of CCTV recordings as evidence in the investigation and proving of criminal cases at the Rembang Police Department and the Rembang District Court is that CCTV recordings are intended to expedite and simplify the process in court proceedings, and are permissible as long as the process is conducted in a manner permitted by regulations and other legal norms. The solution to address this problem is to provide training for members in digital forensics and to seek assistance from the central government, namely the regional police, to bring in experts in the field of digital forensics.